Determinação da densidade de Demodex canis por PCR em tempo real associada à concentração sérica de citocinas e aspectos clínico-patológicos em cães com demodiciose localizada e generalizada - Gasparetto, Naiani Domingos (2017)
Canine demodicosis is a parasitic inflammatory dermatopathy that occurs frequently in the veterinary dermatological routine and is the result of the abnormal proliferation of the Demodex canis mite in the hair follicles and sebaceous glands. It affects young and adult dogs and according to the extent of the lesions can be characterized as localized or generalized. The localized disease seems to be self-limited and progresses to cure. In turn, the widespread form of the disease requires prolonged acaricide therapy, sometimes associated with antibiotic therapy. The reason why the clinical manifestations occurs in only a few animals, as well as the fact that some develop localized demodicosis and others the most severe form of the disease has not been well elucidated, even because it is a commensal mite. The objective of this study was to determine localized and generalized demodicosis mites density on dogs skin and to evaluate the immune response by serum cytokine concentrations, besides observing the disease clinical and histopathological aspects. Fifty-four dogs divided into generalized demodicosis (GD), localized demodicosis (LD) and control group (CG) were submitted to skin scraping, blood collection and skin biopsy. The skin density of D. canis on the canines of this study was established by real-time PCR, the concentrations of IL-1β, IL-6, IL-8, IL-10, IL-12 and TNF by flow cytometry and the skin lesions were observed on histopathological examination. Alopecia, scaling, erythema, and crusting were the most observed clinical alterations and the severity of cutaneous histological lesions in dogs were common to LD and GD groups, with predominance of perifolliculitis. It was possible to establish the amount of D. canis by real-time PCR. The mite density was statistically higher in the LD and GD groups than in healthy dogs. Furthermore, it was observed increased IL-6 serum levels on LD dogs compared to CG. Finally, it was not possible to observe a correlation between the cutaneous amount of D. canis and others serum cytokines levels in the canines of this study. According 9 to the results, it was possible to conclude that pyoderma tends to be the triggering factor of severe dermal microscopic inflammation in demodicosis. It is not possible to differentiate both clinical forms of the disease by histopathological examination. In addition, real-time PCR has been shown to be an important method for obtaining D. canis density on dogs skin and higher amounts of mites are directly related to clinical manifestations. Eventually, IL-6 seems to be induced in the acute inflammatory phase response in canines with localized demodicosis. However, the activity of IL-8, IL-1β, IL-6, IL-10, TNF and IL-12 does not seem to be influenced by the amount of D. canis on the host skin.